Analysis of the socio-economic determinants of consumer rice choice: the case of local and imported rice in Benin - Arouna, A.; Gandonou Migan, J.; Yergo, W.; Gandonou, E. (2024)
Rice consumption in Benin has significantly increased, but the country remains dependent on imports to meet domestic demand. This study aims to analyze the socio-economic determinants of consumer choice of rice locally produced in Benin. To achieve this objective, data were collected from a sample of 901 consumers from 6 markets (2 in South, 2 in Center and 2 in North). We used Kendall's concordance test and the Seemingly Unrelate Regressions SUR bivariate probit model to identify consumer preferences according to rice characteristics, to identify the socio-economic factors influencing household demand for local rice. Results showed that the majority of households consume imported rice and information about local rice encourages households to consume it. Kendall's test revealed that households generally regard the following attributes to be important: taste, cleanliness, swelling capacity, affordable price, and preservation after cooking. These preferences are similar for imported and local rice, but availability is crucial for imported rice, while nutritional benefits are crucial for local rice. Results also showed that on the one hand, the age of the household head, the perceived cleanliness of the rice, and the geographical residence encourage the consumption of local rice. On the other hand, the level of education, female household headship, and the purchase price of rice reduce consumption, indicating price sensitivity and different preferences. It would therefore be useful to study the impact of awareness and information campaigns on local rice consumption habits, especially in urban areas where local rice consumption could be further promoted.